Kurikulum Merdeka Implementation Strategy in Improving the Quality of Learning for Gen Z in Senior High School - Revina Adelia; Suyatno Suyatno; Enung Hasanah (Mitra Edukasi dan Publikasi, 2026)
Improving the quality of learning is a major challenge in Indonesian education, particularly in the era of digital transformation and the dynamic characteristics of Generation Z. The Kurikulum Merdeka is a response to the demands for more flexible, adaptive, and student-centered learning. This study research purposes to explore the implementation strategies of the Kurikulum Merdeka in improving the quality of learning for Generation Z at SMA Muhammadiyah Toboali. This study uses a qualitative approach with a case study design, through data collection techniques such as interviews, observations, and documentation involving the principal, teachers, and students. The findings show that the implementation of the Kurikulum Merdeka at SMA Muhammadiyah Toboali is carried out systematically, collaboratively, and contextually to the needs of students. The principal plays an active role in socializing the curriculum, conducting teacher training, developing a KOSP relevant to school conditions, and conducting digital-based evaluations. Meanwhile, teachers implement differentiated learning, utilize digital technology, and create an interactive and humanistic learning atmosphere. Students experience benefits in the form of increased learning motivation, flexibility in the learning process, and a more personalized assessment experience. In conclusion, the implementation of the Kurikulum Merdeka at Muhammadiyah High School in Toboali demonstrates that a synergistic strategy combining school leadership, teacher learning innovation, and an understanding of Generation Z characteristics can bring about real transformation in the educational process. With an adaptive and contextual approach, the Kurikulum Merdeka not only addresses the challenges of the 21st century but also strengthens the quality of meaningful, relevant, and impactful learning for students. With an adaptive and contextual approach, the Kurikulum Merdeka not only responds to the challenges of the 21st century but also enhances the quality of meaningful, relevant, and impactful learning for students.